2018
DOI: 10.1016/j.jvs.2018.08.151
|View full text |Cite
|
Sign up to set email alerts
|

The 100 most cited articles in the endovascular treatment of thoracic and abdominal aortic aneurysms

Abstract: Objective: Since the introduction of endovascular technology to treat thoracic and abdominal aortic aneurysms, there has been a global research effort focused on assessing the effectiveness of treatment. A bibliometric analysis is used to identify the scientific impact of an article, impactful authors, institutions, and collaborative groups. Our objective was to identify and to analyze the 100 most cited articles in the field of endovascular treatment of thoracic and abdominal aortic aneurysms. Methods: We per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Second, the time factor would also have a definite impact as recently published articles are at a clear disadvantage because of insufficient time to accumulate a relatively greater number of citations irrespective of their content and quality . This can be partially overcome by analyzing the citation density …”
Section: Discussionmentioning
confidence: 99%
“…Second, the time factor would also have a definite impact as recently published articles are at a clear disadvantage because of insufficient time to accumulate a relatively greater number of citations irrespective of their content and quality . This can be partially overcome by analyzing the citation density …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in this study, the papers published in recent years (from 2016 to 2020) were not included in the top 100, but it does not mean those papers are not that important. Second, papers published in journals with higher impact factors may gain greater attention and thus have more citations [ 14 ]. To evaluate any inherent bias, we analyzed the correlation between the number of citations of articles in our list and the impact factors of journals where the papers were published; we also examined the correlation between the number of citations and year of publication.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of minimally invasive treatment, EVAR, a new minimally invasive surgical approach for AAA, has led to global research efforts focused on evaluating the effectiveness of both treatments. The results proved that both open repair (OA) and EVAR were safe and effective in treating AAA [ 23 ], and the long-term survival rate of OA was higher than that of RVAR, as shown by long-term follow-up [ 37 ], and Zhou et al [ 13 ] performed an updated literature measurement analysis. At the same time, our results showed that analysis of risk factors for rupture in terms of blood flow and foundation (intraluminal thrombus, flow, wall stress, inflammation, expression, smooth muscle cells) is also a hot topic of current research.…”
Section: Discussionmentioning
confidence: 99%
“…Bibliometric analysis is an overall analysis of the published literature in a specific research area over a specific time frame [ 11 13 ]. Compared with traditional systematic evaluation, bibliometric analysis focuses on the institution, authorship, and social structure of the literature, providing a timely and intuitive method to explore specific areas [ 14 ].…”
Section: Introductionmentioning
confidence: 99%